Fifty shades of QE: Robust evidence - Brian Fabo; Martina Jancoková; Elisabeth Kempf; éLuboés Pástor (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
Fabo, Jancoková, Kempf, and Pástor (2021) show that papers written by central bank researchers find quantitative easing (QE) to be more effective than papers written by academics. Weale and Wieladek (2022) show that a subset of these results lose statistical significance when OLS regressions are replaced by regressions that downweight outliers. We examine those outliers and find no reason to downweight them. Most of them represent estimates from influential central bank papers published in respectable academic journals. For example, among the five papers finding the largest peak effect of QE on output, all five are published in high-quality journals (Journal of Monetary Economics, Journal of Money, Credit and Banking, and Applied Economics Letters), and their average number of citations is well over 200. Moreover, we show that these papers have supported policy communication by the world's leading central banks and shaped the public perception of the effectiveness of QE. New evidence based on quantile regressions further supports the results in Fabo et al. (2021).
Keywords: A11; E52; E58; G28; 330; Economic research; quantitative easing; QE; central bank; career concerns